Amerindian ancestry and extended longevity in Nicoya, Costa Rica - Azofeifa Navas, Jorge (2018)
Objectives: The aim of this study was to address the hypothesis that Amerindian ancestry is associated with extended longevity in the admixed population of Nicoya, Costa Rica. The Nicoya Peninsula of Costa Rica has been considered a “longevity island,” particularly for males. Methods: We estimated Amerindian ancestry using 464 ancestral informative markers in 20 old Nicoyans aged 99 years, and 20 younger Nicoyans (60-65 years). We used logistic regression to estimate odds ratio (OR) and 95% confidence interval (CI) of the association of Amerindian ancestry and longevity. Results: Older Nicoyans had higher Amerindian ancestry compared to younger Nicoyans (43.3% vs 36.0%, P5.04). Each 10% increase of Amerindian ancestry was associated with more than twice the odds of being long-lived (OR52.32, 95% CI51.03-5.25). Conclusions and Implications: To our knowledge, this is the first time that ancestry is implicated as a likely determinant of extended longevity. Amerindian-specific alleles may protect against early mortality. The identification of these protective alleles should be the focus of future studies.